Синергетичний менеджмент як концепція організованої синергії в управлінні підприємствами - Шевцова, Г.З. (Економіка промисловості, 2012)
Изложены сущность и ключевые положения авторской концепции синергетического менеджмента предприятий. Предложена структурно-функциональная модель синергетического менеджмента, основу которой составляет концепт организованной синергии. Определены особенности функций синергетического управления. Обоснована ключевая роль функции самоорганизации и раскрыты предпосылки самоорганизации производственно-экономических систем. Ключевые слова: синергетический менеджмент, организованная синергия, организация, самоорганизация, управление, функция, предприятие. Викладено сутність та ключові положення авторської концепції синергетичного менеджменту підприємств. Запропоновано структурно-функціональну модель синергетичного менеджменту, основу якої становить концепт організованої синергії. Визначено особливості функцій синергетичного управління. Обґрунтовано ключову роль функції самоорганізації й розкрито передумови самоорганізації виробничо-економічних систем. Ключові слова: синергетичний менеджмент, організована синергія, організація, самоорганізація, управління, функція, підприємство The article describes the essence and key points of the author’s concept of enterprise synergetic management. Modern enterprises are complex selforganizing systems which function under conditions of ambiguity and environment dynamism. Their management mechanisms require a qualitative update. This problem determines the relevance of developing new approaches. A synergetic approach in management is fundamentally different from traditional systems that are based on the external actions towards the object of management. Synergetic management rejects to regulate directly the object behavior in favor of organizing and stimulating its selforganization internal mechanisms. The enterprise’s synergetic management system consists of components that are presented in the form of a structural-functional model. The basis of this model is the concept of organized synergy. The model contains two self-organization loops which reflect the self-regulation and self-development mechanisms of enterprise’s systems. The features of synergetic management functions which include self-organization motivation, synergetic planning and control were determined. The relationship between “organization” and “self-organization” categories was studied. The key role of self-organization function in the enterprise’s synergetic management system was proved. The universal preconditions for self-organization which are required to form synergetic properties for systems of any nature were defined. These preconditions are autonomy and self-sufficiency of subsystems, informational communication and coordinated behavior, motivated integration into the unified system. Specific self-organization preconditions that reveal concrete directions of the self-organization function implementation in enterprise’s systems were justified. The practical application of the above approach allows to influence the mechanisms of self-organization and ensure their qualitative renewal as well as efficiency growth. Keywords: synergetic management, organized synergy, organization, self-organization, management, function, enterprise.